FOSjuice: Fortified Fruit Juice - Zulkali, Mohamad Daud, Assoc. Prof. Dr.; Noor Hasyierah, Mohd Salleh; Alina Rohayu, Mohamed; Ku Syahidah, Ku Ismail; Rohazita, Bahari; Hafizah, Mohd Johar; Hafiza, Shukor; Sriyana, Abdullah (Malaysian Invention and Design Society (MINDS), 2010)
Assoc. Prof. Dr. Mohamed Zulkali Mohamed Daud and his team from School of Bioproses Engineering won silver for FOSjuice Fortified Fruit Juice. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.